Chemical composition optimization of nanocomposites used for shed and core of outdoor composite insulators - Gafti, Abdolah; Taherian, Reza; Kiahoseini, Seyed Rahim (Frontiers in Materials, 2022)
Outdoor 24-kV power transmission insulators include two main pieces, shed and core that in this research are manufactured separately by roll/hot pressing and hand lay-up methods, respectively. Both shed and core are provided from polymer-based composites due to low weight, high strength-to-weight ratio, as well as higher moisture and pollution resistance, in comparison to ceramic and glass sheds. Sheds are made from silicone rubber as matrix and Alumina Trihydrate (ATH) and TiO2 as additives in single-filler and double-filler composites. Characterization tests of sheds include variable voltage tests (max stability voltage) and constant voltage tests (dry, wet, notched max endurance voltage, erosion), and contact angle tests. The analyses establish that the best material for the shed by focusing on the hydrophobicity of sheds is the silicone rubber reinforced 5wt.% TiO2 can be the right candidate for sheds. The core of the insulator is made of epoxy reinforced by different glass fiber percentages of 10, 13, and 15 wt.%. The manufacturing method is hand lay-up. Tensile strength and Scanning Electron Microscopy (SEM) are used for characterization.